2004
DOI: 10.1262/jrd.50.375
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I Overexpression Causes Fetal Loss during Placentation in Mice

Abstract: Abstract.To understand the role of IGF-I in murine pregnancy, we studied the reproductive performance of IGF-I overexpressed mice. Fetal loss occurred only in the transfected uterine horn during Day 10-15 of pregnancy. The placenta appeared healthy until Day 10 of pregnancy. From Day 12, the decidua basalis of the transfected horn increased in thickness. The vascular lumen was expanded, and most of embryos were dead. Uterine Natural Killer cells did not undergo apoptosis from Day 10 to Day 15 when they usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…We reported that dNK cells from patients who underwent spontaneous abortions showed lower miR-483-3p expression, which correlated well with increased IGF-1 production, perforin expression and cytotoxic activity when compared with dNK cells from healthy controls. It has been reported that IGF-1 overexpression can cause fetal loss during placentation in mice; these high levels of IGF-1 could directly alter the characteristics and functions of the uterine NK cells46. Our histological analysis data also show that IGF-1 expression is higher in decidual tissues from patients with spontaneous abortions than in tissues from healthy controls in vivo (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 72%
“…We reported that dNK cells from patients who underwent spontaneous abortions showed lower miR-483-3p expression, which correlated well with increased IGF-1 production, perforin expression and cytotoxic activity when compared with dNK cells from healthy controls. It has been reported that IGF-1 overexpression can cause fetal loss during placentation in mice; these high levels of IGF-1 could directly alter the characteristics and functions of the uterine NK cells46. Our histological analysis data also show that IGF-1 expression is higher in decidual tissues from patients with spontaneous abortions than in tissues from healthy controls in vivo (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 72%
“…We suggest that PF-E inhibited the development of preimplantation embryos by impacting the function of embryo-derived factors rather than directly impairing their synthesis and secretion. On the other hand, although growth factors are important for fetal development, their overexpression may also have adverse effects (35). The mechanism involved in this abnormal increase of embryonic growth factors is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Placental morphogenesis accompanied with trophoblast development may be associated with the apoptosis of uNK cells through the regulation of FasL release. I n i n s u l i n -l i k e g r o w t h f a c t o r ( I G F ) -1 overexpressing mice, apoptosis of uNK cells is clearly inhibited, and moreover, fetal loss is frequently occurred following the progress of pregnancy [21]. This report estimated a functional necessity of uNK cells in the normal process of successful pregnancy.…”
Section: Discussionmentioning
confidence: 73%